Preliminary X-ray diffraction analysis of CfaA, a molecular chaperone essential for the assembly of CFA/I fimbriae of human enterotoxigenic Escherichia coli - Bao, Rui (International Union of Crystallography, 2014)

(untitled)
Understanding of pilus bioassembly in Gram-negative bacteria stems mainly from studies of P pili and type 1 fimbriae of uropathogenic Escherichia coli, which are mediated by the classic chaperone–usher pathway (CUP). However, CFA/I fimbriae, a class 5 fimbria and intestinal colonization factor for enterotoxigenic E. coli (ETEC), are proposed to assemble via the alternate chaperone pathway (ACP). Both CUP and ACP fimbrial bioassembly pathways require the function of a periplasmic chaperone, but their corresponding proteins share very low similarity in primary sequence. Here, the crystallization of the CFA/I periplasmic chaperone CfaA by the hanging-drop vapor-diffusion method is reported. X-ray diffraction data sets were collected from a native CfaA crystal to 2 Å resolution and to 1.8 and 2.8 Å resolution, respectively, from a lead and a platinum derivative. These crystals displayed the symmetry of space group C2, with unit-cell parameters a = 103.6, b = 28.68, c = 90.60 Å, β = 119.7°. Initial phases were derived from multiple isomorphous replacement with anomalous scattering experiments using the data from the platinum and lead derivatives. This resulted in an interpretable electron-density map showing one CfaA molecule in an asymmetric unit. Sequence assignments were aided by anomalous signals from the heavy-atom derivatives. Refinement of the atomic model of CfaA is ongoing, which is expected to further understanding of the essential aspects and allowable variations in tertiary structure of the greater family of chaperones involved in chaperone–usher mediated bioassembly.